Tree diversity and canopy cover in cocoa systems in Ghana - Asare, R.; Anders, R. (Springer, 2016)
Cocoa (Theobroma cacao L.) growing systems in Ghana and West Africa consist of diverse tree species and densities. This study was conducted to determine factors that influence tree species configurations and how tree characteristics affect canopy cover in cocoa farms. Eighty-six farmers and corresponding farms were selected in a systematic approach in four districts across two agro-ecological zones in Ghana. Results show that men tend to have larger farm sizes, higher tree density and diversity than women. Tree density and canopy cover of shade trees were low on large farms, but diversity increased with increasing farm sizes. Even though there was a significant correlation between diameter at breast height and crown area for all species investigated, tree species differed considerably in their crown area and thus the amount of ground cover provided. Current recommendations for shade are usually expressed in number of trees per ha, and our results suggest that these should be refined to reflect the effects of species, the size of their diameter at breast height and the crown area.